A flexible metallic TiC nanofiber/vertical graphene 1D/2D heterostructured as active electrocatalyst for advanced Li–S batteries - Zhang, Yongshang; Zhang, Peng; Zhang, Shijie; Wang, Zheng; Li, Neng; Silva, S. Ravi P.; Shao, Guosheng (InfoMat, 2021)
The realistic application of lithium–sulfur (Li–S) batteries has been severely hindered by the sluggish conversion kinetics of polysulfides (LiPS) and inhomogeneous deposition of Li2S at high sulfur loading and low electrolyte/sulfur ratio (E/S). Herein, a flexible Li–S battery architecture based on electrocatalyzed cathodes made of interfacial engineered TiC nanofibers and in situ grown vertical graphene are developed. Integrated 1D/2D heterostructured electrocatalysts are realized to enable highly improved Li+ and electron transportation together with significantly enhanced affinity to LiPS, which effectively accelerate the conversion kinetics between sulfur species, and thus induce homogeneous deposition of Li2S in the catalyzed cathodes. Consequently, highly active electro‐electrocatalysts‐based cells exhibit remarkable rate capability at 2C with a high specific capacity of 971 mAh g−1. Even at ultra‐high sulfur loading and low E/S ratio, the battery still delivers a high areal capacity of 9.1 mAh cm−2, with a flexible pouch cell being demonstrated to power a LED array at different bending angles with a high capacity over 100 cycles. This work puts forward a novel pathway for the rational design of effective nanofiber electrocatalysts for cathodes of high‐performance Li–S batteries. Novel method was developed for in situ growth of vertical graphene with simultaneous conversion of the substrate TiO2 nanofibers into TiC ones, with well‐interconnected interfaces within the metallic VG/TiC 1D/2D heterostructured electrocatalyst enabling fast redox kinetics essential for Li–S cells. This work offers a novel avenue for the fabrication of high‐performance cathode critical to practical high‐energy‐density Li–S batteries.